2017
DOI: 10.1016/j.ekir.2016.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Profiling of Plasma Metabolites Suggests Altered Mitochondrial Fuel Usage and Remodeling of Sphingolipid Metabolism in Individuals With Type 2 Diabetes and Kidney Disease

Abstract: IntroductionPathophysiology of diabetic kidney disease (DKD) is incompletely understood. We aim to elucidate metabolic abnormalities associated with DKD in type 2 diabetes mellitus (T2DM) by targeted plasma metabolomics.MethodsA total of 126 T2DM participants with early DKD (urinary albumin-to-creatinine ratio [ACR] 30−299 mg/g and eGFR ≥ 60 ml/min/1.73 m2), 154 overt DKD (ACR ≥ 300 mg/g or eGFR < 60 ml/min/1.73 m2), and 129 non-DKD T2DM controls (ACR < 30 mg/g and eGFR ≥ 60 ml/min/1.73 m2) were included in di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
66
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(75 citation statements)
references
References 47 publications
(74 reference statements)
7
66
2
Order By: Relevance
“…This would lead to accumulation of fatty acid fuels in the mitochondria and contribute to insulin resistance via the mismatching of fuel and ATP demand. 45 While we did not observe significant associations between medium-chain species and diabetes risk following multiple testing correction, it has been suggested that the accumulation of medium-chain species results in activation of the proinflammatory NFκB pathway, which in turn promotes insulin resistance. 44 The accumulation of long-chain species, such as C16-OH, is similarly thought to be reflective of impaired tricarboxylic acid cycle activity, as they are the initial products of βoxidation.…”
Section: Discussioncontrasting
confidence: 64%
“…This would lead to accumulation of fatty acid fuels in the mitochondria and contribute to insulin resistance via the mismatching of fuel and ATP demand. 45 While we did not observe significant associations between medium-chain species and diabetes risk following multiple testing correction, it has been suggested that the accumulation of medium-chain species results in activation of the proinflammatory NFκB pathway, which in turn promotes insulin resistance. 44 The accumulation of long-chain species, such as C16-OH, is similarly thought to be reflective of impaired tricarboxylic acid cycle activity, as they are the initial products of βoxidation.…”
Section: Discussioncontrasting
confidence: 64%
“…Liu et al . () performed a targeted plasma metabolomic study, whose findings were somehow in agreement with the findings by Niewczas et al . () that amino acids or their derivatives are associated with the risk of progression to ESRD.…”
Section: Diabetic Nephropathysupporting
confidence: 88%
“…The amino acid derivative most positively associated with progression to ESRD was C-glycosyltryptophan, odd ratio of 6.6 (95% CI: 2.8, 15). Liu et al (2017) performed a targeted plasma metabolomic study, whose findings were somehow in agreement with the findings by Niewczas et al (2014) that amino acids or their derivatives are associated with the risk of progression to ESRD. Metabolic pathways related to DKD in an Asian T2DM population were studied by analyzing 123 plasma metabolites using LC-MS and GC-MS.…”
Section: B Investigations On Plasma Proteome and Metabolome In Dkdsupporting
confidence: 73%
“…2A). Increased SM levels in relation with CKD were also reported in individuals with Type 1 Diabetes (T1D) (33) and T2D (34), except for the non-targeted lipidomic study of T1D (35). Isomer annotation of the top significant metabolite SM C18:1 in our study revealed that it may consist of several sphingoid backbones (d16:1, d18:0, d18:1, d18:2, d19:1) bound to mainly saturated or monounsaturated fatty acyls with 16-18 carbons (36).…”
Section: Discussionmentioning
confidence: 91%